2018
DOI: 10.1136/openhrt-2018-000814
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in exhaled hydrogen as marker of congestive heart failure

Abstract: ObjectiveHydrogen excretion is thought to be related to systemic antioxidation activity. H2 selectively reduces the hydroxyl radical of free hydrogen (·OH), a highly cytotoxic form of reactive oxygen species, in cultured cells.MethodsWe investigated whether exhaled H2 decreased during night sleep, reflected ·OH production and was associated with heart failure severity. We enrolled 108 patients with chronic heart failure (CHF) and 15 control participants without CHF. H2 concentration was measured by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Thus, given antibiotics for 4 days by mixing penicillin and streptomycin in the drinking water can reduce the H 2 concentration below the 1-ppm detection limit in the expired air of male C57BL/6J mice, and the infarct size was significantly higher in mice administered with antibiotics than that in antibiotics non-treated mice (Shinbo et al, 2013). Another clinical investigation recently revealed overnight change in H 2 concentration (ΔH 2 ) was significantly lower in patients with chronic heart failure compared with controls and was positively correlated with cardiac index (Shibata et al, 2018). Ostojic also proposed an idea that an impaired production of endogenous H 2 by intestinal microbiota might play a role in Parkinson disease pathogenesis (Ostojic, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, given antibiotics for 4 days by mixing penicillin and streptomycin in the drinking water can reduce the H 2 concentration below the 1-ppm detection limit in the expired air of male C57BL/6J mice, and the infarct size was significantly higher in mice administered with antibiotics than that in antibiotics non-treated mice (Shinbo et al, 2013). Another clinical investigation recently revealed overnight change in H 2 concentration (ΔH 2 ) was significantly lower in patients with chronic heart failure compared with controls and was positively correlated with cardiac index (Shibata et al, 2018). Ostojic also proposed an idea that an impaired production of endogenous H 2 by intestinal microbiota might play a role in Parkinson disease pathogenesis (Ostojic, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to sample size differences since our study comprised 240 patients compared to only 12 of Jonderko et al In any case, H 2 range across different days was reduced (although not significantly) when looking in those tests performed at same time of day (less than 60 min apart), suggesting that at least some of the variability observed can be attributed to the time of the day the test is performed. Shibata et al 25 found in healthy controls slightly higher levels (an increase of 2 ppm) of fasting H 2 in the morning than before sleep the previous night. Related to this, we should consider that during the night there is a nocturnal hypoventilation that can cause these slightly elevated fasting levels of breath H 2 produced by persisting fermentable substrates in the colon 26 .…”
Section: Discussionmentioning
confidence: 94%
“…The lactose that cannot be degraded is not absorbed in the small intestine and is fermented by intestinal bacteria in the large intestine, and H 2 is produced. The produced H 2 is absorbed through the intestinal mucosa, dissolved into the blood, and diffused into the alveoli via the blood circulation, and some of it is expired in the exhaled air [12]. Lactose also irritates the large intestine, causing the abdominal symptoms of lactose intolerance.…”
Section: Discussionmentioning
confidence: 99%